Establishment of human amniotic fluid stem cells from full-term pregnancies - Joharry, Muhammad Khair (2019)
Cells in human amniotic fluid (AF) are heterogeneous and they harbor stem cells with high differentiation spectrum. Although mid-term AF has been proven to have highly potent stem cell population, it is still uncertain whether AF of full-term pregnancy harbour these cell types. Hence, this study aims to explore the possibility of isolating and establishing highly potent stem cells from human AF harvested during deliveries. Samples collected were through artificial rupture membrane (ARM), and caesarean section (C-Sect) deliveries at 38-40 weeks gestation period together with amnioreduction (AR) from mid-term gestation (as a positive control) were cultured and propagated. Time taken for all samples to become confluent and cell morphology were evaluated. Cell viability and population doubling time were examined. C-Sect samples were found to take faster time reaching confluency compared to ARM samples with both have similar cell morphology in Amniomax medium. These results show the presence of viable cells in full-term AF. These findings put significant hopes for the existence of stem cell in AF during deliveries, which normally would be discarded. The isolation of high potency stem cells was then carried out by EasySep method using magnetic assorted cell sorting technique. The sorted cells which are the c-Kit positive cells were then cultured and enriched to increase the total cell count. The cells were then further characterized for the expression of pluripotency-associated markers, population doubling time and the formation of embryoid bodies. OCT4, NANOG and c-Kit expressions were observed in C-Kit positive cells at both RNA and protein levels. The population doubling time (PDT) for the c-Kit positive cells were 30-50 hrs. The EBs formed were in good shape having smooth boundaries and diameters of 150-300μm. Upon prolonged culture of EBs, these cells demonstrated the ability to spontaneously differentiate into derivatives of the three primary germ layers based on specific markers expression for endodermal, mesodermal and ectodermal lineages. EBs were stained with Albumin for endodermal lineages at day 21 post-differentiation, whereas Bracyhury for mesodermal and class III Beta tubulin for ectodermal lineages were expressed at day eight post-differentiation. The C-Kit positive cells managed to survive up until passage 10-14 before they became senescent. All findings highly indicate the success of the establishment of highly potent stem cell from full term AF.